Imagining Investigations in Young Children with Autism Spectrum Disorder, without the use of Sedation: Array - Ștefănescu, Cristina (New Trends in Psychology, 2021)
There have been several cases of children with autism spectrum disorder investigated at the department of Radiology, at St. John Hospital for Children, for four type of imaginig methods: radiography, ecography, CT and MRI. I conducted a study of 45 children, who came during a year for these four types of imagining investigations. The duration of the investigation determined their reaction, half of them cooperated well with the doctors when radiographies, CTs and ecographies needed to be carried out, where the investigation didn`t take more than ten minutes. Concerning the MRI investigation, that take up to one hour, half of the children, 50% needed to be sedated with melatonin, while 30% required general anaesthesia, 20% managed to comply while the parents sang to them, or they stood awake a night before the investigation and they were tired.